PROBLEMS AND OBSTACLES IN APPLYING FOR PERMISSION TO RUN AN ANTIQUES TRADING BUSINESS - Wongchanapai, Uthai (Journal of MCU Nakhondhat, 2023)
This research article is a case study on the problems and obstacles of Applying for permission to operate an antiques trading business under the Auction and Antiques Trading Control Act, B.E. 1931 with the following objectives: 1) To analyze the problems and obstacles in obtaining an antiques business license under the Auction and Antiques Trading Control Act; and 2) To find appropriate ways to solve problems and obstacles in obtaining an antiques business license in Thailand to suit the current situation. This research is a research in the form of secondary data, most of which are documentary data. in order to process and analyze the information about the causes of problems and obstacles related to applying for permission to operate an antiques trading business in Thailand By researching and collecting information from textbooks, articles, theses and academic literature. and a comparative study with the laws of foreign trade antiques, namely the Federation of Malaysia and the Republic of Singapore which can be regarded as a developed country and has an area adjacent to Thailand which will be beneficial in further amending such laws From the results of the research, it was found that the problems and obstacles in obtaining permission to operate antiques trading business in Thai society currently have the following important issues: 1) in terms of definitions that are not clear and comprehensive enough to cause problems in interpretation; 2) in terms of properties or Conditions for applying for an antique business license due to obsolescence 3) Merging two types of businesses into the same law, although the nature of the business operations are clearly different. As a result, law enforcement is inefficient.